The Concept of Religious Tolerance in Indonesia According to Buya Hamka in Tafsir Al-Azhar - Nurlina Nurlina; Busro Busro (Gunung Djati Conference Series, 2021)
This study aims to discuss the concept of religious tolerance according to Hamka in Tafsir al-Azhar. This study uses qualitative methods and thematic interpretation approaches. The result of this discussion is that the concept of religious tolerance according to Hamka is to treat adherents of other religions in a good and fair manner with restrictions not to mix Islamic beliefs with other religions. This study concludes that with the existence of religious diversity in Indonesia, the concept of religious tolerance according to Hamka is a solution to improve people's understanding of differences. This study also recommends that in-depth research be carried out regarding the latest issues of religious conflict combined with the concept of tolerance in order to minimize religious conflicts and provide factual solutions for the community.